Human basal cell carcinoma: the induction of anagen hair follicle differentiation. (1st April 2020) - Morgan, H. J.; Benketah, A.; Olivero, C.; Rees, E.; Ziaj, S.; Mukhtar, A.; Lanfredini, S.; Patel, G. K.
Summary: Background: Consistent with cancer stem cell driven pattern of growth, human basal cell carcinomas (BCCs) demonstrate differentiation along hair follicle (HF) lineages. Aim: To define the pattern of differentiation and therapeutic targets that promote BCC differentiation and therefore BCC cancer stem cell exhaustion. Methods: An alkaline phosphatase substrate kit was used to determine dermal papilla cells within the BCC stroma. Autonomous HF cycle‐dependent gene expression was identified by analysis of the human homologues of a murine gene set (total 2289 genes) that is differentially expressed in hair cycle phases. The findings were validated by quantitative real‐time PCR and immunofluorescence, as well as in vitro transforming growth factor (TGF)‐β2 stimulation of BCC cancer stem cell colonies. Results: As in the HF, keratin expression in the inner root sheath and matrix in BCC correlated with proliferative index and was tightly regulated, despite the absence of dermal papilla cells. Cross‐species microarray analysis comparing human BCC and murine synchronous HF growth cycle datasets revealed 74% concordance with telogen differentiation compared with anagen (23%, P < 0.01) and catagen (49%; P < 0.01). Incomplete anagen differentiation within BCC was characterized by reduced expression of the anagen master regulator DLX3 (−5.5‐fold), and increased expression of telogen‐associated genes: AEBP1 (2.2‐fold), DEFB8 (35.3‐fold), MMP3 (106.0‐fold) and MMP12 (12.9‐fold). Restoration of dermal papilla signals by in vitro addition of TGF‐β2 enhanced anagen differentiation. Conclusion: Our findings show that BCC cells differentiate along HF lineages and may be susceptible to exogenous HF cycle modulators.